Exploring Health Effects of 6 and 15 MV X-ray Photons in Breast Cancer Therapy on heart and lung - Hassan Saberi; Mahshad Neshasteriz; Ahad Zeinali; Mohsen Hoseini; Laya Karimkhani (Health Science Monitor)
Background & Aims: In cancer patients, radiation therapy is vital but can lead to long-term side effects due to exposure of healthy tissues. This study focuses on breast cancer patients, where unintended radiation can affect organs like the heart and lung. This study investigates how photon radiation energy impacts dose distribution in tumors, heart, and lung post-radiation therapy. Materials & Methods: Data from computed tomography (CT) scans of 20 female breast cancer patient’s post-mastectomy were analyzed. Treatment plans using 6 and 15 Mega-Volts (MV) energies for each patient were compared. The study considered a dose of 5000 cGy for each patient, evaluating conformity and homogeneity in the target volume, alongside average doses to sensitive organs using dose-volume histograms (DVH). Results: The results indicated that 15 MV energy reduced heart and lung doses compared to 6 MV during breast radiation therapy. Average heart doses at 6 and 15 MV were 706.15 and 630.35 cGy, respectively, and lung doses were 1630.05 and 1555.03 cGy, respectively. While 15 MV energy benefited organ doses, 6 MV provided better uniformity and homogeneity in dose distribution within the target volume. Conclusion: This study demonstrated significant differences in the dose received by organs at risk such as the heart and lung during radiation therapy with different photon energies, highlighting the importance of selecting the appropriate energy in safeguarding and health of vital organs.